Element migration and hydrothermal alteration of the Tuwaishan orogenic gold deposit in West Hainan Island, South China - Liu, Yu-Heng; Mao, Jingwen; Hu, Jun; Ma, Jia-Dong; Wang, Lei; Xu, De-Ming; Zhao, Zhao-Xia; Bishikwabo, Germain Kaningu; Gamboa-Herrera, J.A.; Fan, Chang; Yu, Hao-Cheng (Ore geology reviews, 2025)
[Display omitted] •Mass balance calculations reveal element migration in ores and altered rocks of the Tuwaishan orogenic gold deposit.•Molybdenum is separated from W and Au during gold mineralization of the Tuwaishan gold deposit.•Metamorphism of the Ordovician-Silurian sedimentary rocks led to the formation of the Gezhen shear zone gold deposits. The Tuwaishan orogenic gold deposit, located in the western part of Hainan Island, South China, is a structurally controlled gold deposit formed during the Triassic. It is one of several gold deposits hosted within Mesoproterozoic terranes, primarily granitoids with minor contributions from schists and gneisses. The source of ore-forming fluids and materials for these deposits remains a subject of debate. This study investigates the trends and magnitude of element migration in ores and altered wall rocks during gold mineralization and associated hydrothermal alteration, using mass balance calculations based on new geochemical data from ores and altered samples at the Tuwaishan gold deposit. Our results reveal significant enrichment in SiO2, K2O, Au, Ag, As, Bi, Pb, Cd, Cu, W, Sb, Zn, In, Tl, Cs, Rb, V, Zr, Hf, and Eu, alongside notable depletion in TFe2O3, FeO, Na2O, Mo, Sr, Sc, Co, and Ni. In contrast, no measurable mass change was observed for TiO2, Nb, and Ga. Additionally, we document the geochemical separation of Mo from W and Au within the Tuwaishan gold deposit. Our findings indicate that the iron contributing to sulfide mineral precipitation was entirely derived from granitic mylonites during fluid-wall rock interactions, with the alteration of biotite to chlorite representing the dominant alteration process in the deposit. We propose that metamorphism of Ordovician-Silurian sedimentary rocks at depth, triggered by the collision between the South China and Indochina blocks, provided the ore-forming fluids, gold, and associated metals responsible for the formation of the Gezhen shear zone gold deposits. Furthermore, we suggest that phase separation and water–rock interactions were the primary mechanisms controlling gold precipitation at the Tuwaishan deposit. These findings provide new insights into the formation of Phanerozoic orogenic gold deposits hosted in Precambrian terranes.